Cardiac Arrest Disrupts Caspase-1 and Patterns of Inflammatory Mediators Differently in Skin and Muscle Following Localized Tissue Injury in Rats: Insights from Data-Driven Modeling - Starzl, Ravi; Wolfram, Dolores; Zamora, Ruben; Jefferson, Bahiyyah; Barclay, Derek; Ho, Chien; Gorantla, Vijay; Brandacher, Gerald; Schneeberger, Stefan; Andrew Lee, W. P.; Carbonell, Jaime; Vodovotz, Yoram (Frontiers in Immunology, 2015)
Background: Trauma often co-occurs with cardiac arrest and hemorrhagic shock. Skin and muscle injuries often lead to significant inflammation in the affected tissue. The primary mechanism by which inflammation is initiated, sustained, and terminated is cytokine-mediated immune signaling, but this signaling can be altered by cardiac arrest. The complexity and context sensitivity of immune signaling in general has stymied a clear understanding of these signaling dynamics. Methodology/Principal findings: We hypothesized that advanced numerical and biological function analysis methods would help elucidate the inflammatory response to skin and muscle wounds in rats, both with and without concomitant shock. Based on multiplexed analysis of inflammatory mediators, we discerned a differential interleukin (IL)-1α and IL-18 signature in skin vs. muscle, which was suggestive of inflammasome activation in the skin. Immunoblotting revealed caspase-1 activation in skin but not muscle. Notably, IL-1α and IL-18, along with caspase-1, were greatly elevated in the skin following cardiac arrest, consistent with differential inflammasome activation. Conclusions/Significance: Tissue-specific activation of Caspase-1 and the NLRP3 inflammasome appear to be key factors in determining the type and severity of the inflammatory response to tissue injury, especially in the presence of severe shock, as suggested via data-driven modeling.